A novel approach for detection and quantification of magnetic nanomarkers using a spin valve GMR-integrated microfluidic sensor. Issue 63 (10th July 2015) - Devkota, J.; Kokkinis, G.; Berris, T.; Jamalieh, M.; Cardoso, S.; Cardoso, F.; Srikanth, H.; Phan, M. H.; Giouroudi, I.
<x xml:space="preserve">Abstract</x> We demonstrate the application of a spin valve giant magneto-resistance (GMR) integrated microfluidic sensor for the detection and quantification of superparamagnetic nanomarkers.